Aplikasi Monitoring Aktivitas Layar Komputer Dengan Studi Kasus Lab Praktikum - Kelvin Yohanes; Lily Puspa Dewi; Alexander Setiawan (Jurnal Infra, 2021)
Computer Screen Activity Monitoring Application is an application that used to help supervisors or lecturers or laboratory officers when supervise practical activity, in this case Multimedia (MM) laboratory. With this monitoring application, can capture screenshot of student’s computer without known by the student. So that supervisors or lecturers or laboratory officers can be assisted in supervising practical activities. For the implementation and the usage of this application at MM laboratory, there are two main entities, namely admin or lecturer’s side and client or student’s side. On admin or lecturer’s side, there are user interface and place that used to store screenshot of student’s computer screen. So, on admin or lecturer’s side, can see the screenshot image of student’s computer screen at certain period. On client or student’s side, there are no user interface, because on it’s side, only has background process. This background process only capture screenshot at certain time, then send it to admin or lecturer’s computer. So, admin or lecturer can see the result of captured screenshot from student’s computer. The result of this test shows that this application was running as expected. Background process that’s installed on student’s computer successfully capture screenshot image and send it to admin or lecturer’s computer. Other than that, on admin or lecturer’s side, can see the result. When testing the implementation of this application on MM laboratory, there is a little trouble. The trouble is on Firewall configuration that cannot connect between admin or lecturer’s computer and client or student’s computer. This research can be developed by making other platforms besides Windows, because apart from the MM lab, there are computers with operating systems other than Windows.